Non-invasive markers of airway inflammation as predictors of oral steroid responsiveness in asthma. Issue 3 (1st March 2000) - Little, Stuart A; Chalmers, George W; MacLeod, Kirsten J; McSharry, Charles; Thomson, Neil C
Abstract : BACKGROUND: Sputum eosinophil counts and exhaled nitric oxide (NO) levels are increased in asthma and both measurements fall in response to corticosteroids. METHODS: Exhaled NO levels and sputum eosinophil counts were assessed as non-invasive markers of the response to an oral steroid in 37 patients (19 women) with stable chronic asthma (mean (SD) age 48.6 (12.2) years, asthma duration 25.9 (17.3) years, and baseline forced expiratory volume in one second (FEV1 ) 76.3 (21.9)% predicted). Spirometric tests, with reversibility to a β agonist (2.5 mg nebulised salbutamol), and induced sputum (using nebulised 3% saline) were performed at recruitment and following treatment with 30 mg prednisolone/day for 14 days. RESULTS: Baseline NO levels correlated with the percentage improvement in FEV1 from baseline to the post-steroid, post-bronchodilator value ( r s = 0.47, p = 0.003), with an NO level of >10 ppb at baseline having a positive predictive value of 83% for an improvement in FEV1 of ⩾15% (sensitivity 59%, specificity 90%). Sputum eosinophilia (⩾4%) had a positive predictive value of 68% (sensitivity 54%, specificity 76%) for an increase in FEV1 of ⩾15%. A combination of sputum eosinophilia and increased NO levels resulted in a positive predictive value of 72% and a negative predictive value of 79% (sensitivity 76%, specificity 75%). CONCLUSION: Exhaled NO levels and sputum eosinophilia may be useful in predicting the response to a trial of oral steroid in asthma.